Towards a better understanding of Fagopyrum dibotrys: a systematic review - Le-Le Zhang; Yan He; Feiya Sheng; Ying-Fan Hu; Yu Song; Wei Li; Jiarong Chen; Jinming Zhang; Liang Zou (BMC, 2021)
Abstract Fagopyrum dibotrys (F. dibotrys) (D.Don) H.Hara is a well-known edible herbal medicine in Asian countries. It has been widely used for the treatment of lung diseases, swelling, etc., and is also an important part of many Chinese medicine prescriptions. At present, more than 100 compounds have been isolated and identified from F. dibotrys, and these compounds can be primarily divided into flavonoids, phenols, terpenes, steroids, and fatty acids. Flavonoids and phenolic compounds are considered to be the main active ingredients of F. dibotrys. Previous pharmacological studies have shown that F. dibotrys possesses anti-inflammatory, anti-cancer, anti-oxidant, anti-bacterial, and anti-diabetic activities. Additional studies on functional genes have led to a better understanding of the metabolic pathways and regulatory factors related with the flavonoid active ingredients in F. dibotrys. In this paper, we systemically reviewed the research advances on the phytochemistry and pharmacology of F. dibotrys, as well as the functional genes related to the synthesis of active ingredients, aiming to promote the development and utilization of F. dibotrys.